FRI0339 Sledai-2k responder index-50 is effective in demonstrating partial response in a phase 2, randomised placebo-controlled study of ustekinumab in patients with active systemic lupus erythematosus. (12th June 2018) - Touma, Z.; Urowitz, M.B.; Gladman, D.D.; Wagner, C.; Hsu, B.; Chevrier, M.; Rose, S.; Zhou, B.; Gordon, R.
Abstract : Background: Ustekinumab (UST), a monoclonal antibody that targets shared p40 subunit of cytokines IL-12 and IL-23, is being investigated in pts w/active systemic lupus erythematosus(SLE). While traditional SLE Disease Activity Index 2000(SLEDAI-2K)scoring assesses complete SLE response for individual disease manifestations, SLEDAI-2K Responder Index-50(S2K RI-50)can be used to evaluate SLE responses using partial improvement(≥50%)in each domain. Objectives: To evaluate SLEDAI-2K vs S2K RI-50 response in a randomised, PBO-controlled trial of UST in pts w/active SLE. Methods: We conducted a Ph2, PBO-controlled study in adults w/active disease(SLEDAI score ≥6 w/≥1 BILAG A and /or ≥2 BILAG B scores)despite standard-of-care therapy. Pts(n=102)were randomised(3:2) to UST IV~6 mg/kg or PBO at wk0, followed by SC inj of UST 90 mg q8w or PBO beginning at wk8, both added to standard-of-care. We calculated S2K RI-50 response at wk24 using various thresholds to define response including decrease of at least 1, 2, 3, 4, 5, or6 points from baseline(BL) in S2K RI-50 score. We also compared proportion of pts w/SLEDAI-2K response vs S2K RI-50 response in pts receiving UST(n=62)vs PBO(n=40)at wk24. Results: Change from BL SLEDAI-2K and S2K RI-50 scores were strongly correlated(R=0.89, p<0.0001)at wk24. A greater proportion of UST vs PBO pts achieved S2K RI–50 response at wk24, regardless of threshold used to define response (table 1). The greatest differences in S2K RI–50 response rates between UST vs PBO were observed for a 4-point decrease(23.1%, p=0.010), a 5-point decrease(26.8%, p=0.010), and 6-point decrease (25.5%;p=0.016) from BL. S2K RI-50 captured more responders than SLEDAI-2K at wk24, however, the difference in SLEDAI-2K 4-point response in UST vs PBO was ▵27%(p=0.005)while S2K RI-50 was ▵23%(p=0.010). Conclusions: S2K RI-50 is an instrument that can capture partial clinically important improvement of ≥50% in SLE disease manifestations. The data suggests cutpoints for defining S2K RI-50 response in clinical trials of pts w/moderate-severe SLE disease activity. Disclosure of Interest: Z. Touma Grant/research support from: Janssen Research and Development, LLC, M. Urowitz Grant/research support from: Janssen Research and Development, LLC, D. Gladman Grant/research support from: Janssen Research and Development, LLC, C. Wagner Employee of: Janssen Research and Development, LLC, B. Hsu Employee of: Janssen Research and Development, LLC, M. Chevrier Employee of: Janssen Research and Development, LLC, S. Rose Employee of: Janssen Research and Development, LLC, B. Zhou Employee of: Janssen Research and Development, LLC, R. Gordon Employee of: Janssen Research and Development, LLC